Sewage pollution, declining ecosystem health, and cross-sector collaboration. (March 2021) - Wear, Stephanie L.; Acuña, Vicenç; McDonald, Rob; Font, Carme
Abstract: It is well established that a global sanitation crisis threatens humans. By comparison, much less attention has been given to address the effects of this crisis on the health of ecosystems. We provide examples of how sewage can affect natural ecosystems and where hotspots in sewage contamination commonly overlap with these habitats. We highlight these issues for some of the major ecosystems spanning across terrestrial, aquatic, and coastal realms. Recent studies reveal that untreated and poorly treated sewage elevates concentrations of nutrients, pathogens, endocrine disruptors, heavy metals, and pharmaceuticals in natural ecosystems. We show many large areas (10, 000's of km 2 ) across the globe with high levels of sewage contamination and that these contamination hotspots overlap extensively in occurrence with coral reefs, salt marshes, and fish-rich river systems. Given the global extent of sewage pollution in and near natural habitats, conservation biologists and managers must address this threat. However, because of its size, conservationists cannot solve this problem alone. We therefore argue that conservation must combine forces with the human health sector to create cross-disciplinary synergisms in innovation and efficiency. New sewage management solutions are emerging, such as waste-free toilets and resource recovery to generate fuel and drinking water; but more innovation is needed - a demand that will most effectively be reached through cross-sector collaboration. Highlights: Sewage pollution hotspots are common and occur globally. Studies warn sewage pollution threatens biodiversity and ecosystem health. A mapping exercise highlights global hotspots in sewage pollution commonly occur in terrestrial, aquatic, and marine systems. Mitigating sewage pollution must be prioritized by both the conservation and public health sectors.